New Railway Tunnels and their Construction Method as Well as their Impact to Train Operation - Kalender, Murat; Vojtek, Martin (My University, 2021)
As the modernisation of the cities, railway road construction and modernisation of existing lines are demanded during the past decades more than before. Demand of short travel time is one the reasons that we redesign of existed railway roads and modernisation process. Tunnel construction is one the ways that we can shorten travel time in the existing railway roads. In this study, we introduced one of the commonly used tunnel construction methods, New Austrian Tunnelling Method (NATM), and some of important points of that method regarding tunnel excavation and bearing capacity of excavation support system. Furthermore, we gave some information about some tunnels which shortens the travel time and some tunnel project examples which are constructed with this method. The main purpose of construction of all these tunnels are to shorten the travel time of the existing railway line due to increasing on population and urbanization.
Nové železniční tunely a metody jejich konstuování a jejich vliv na provoz vlaků
Keywords: railways; tunnels; NATM; operation